A Pilot Study Evaluating Antimicrobial Antagonism in Syphilis/Chlamydia trachomatis Co-Infection in Men Who Have Sex with Men - Richardson, Daniel; Siddiqi, Ali; Parashar, Kuhuk; Fitzpatrick, Colin; Pinto-Sander, Nicolas; Goldmeier, David (European Journal of Therapeutics, 2023)
-